EVALUATION OF THE QUALITY OF ACADEMIC INFORMATION SYSTEM UNSOED USING ISO 9126 AND MEAN OPINION SCORE (MOS) - Nofiyati Nofiyati; Arief Kelik Nugroho; Bangun Wijayanto (Informatika, Universitas Jenderal Soedirman, 2022)
Academic Information System is a very important system in assisting the academic process in Higher Education. Jenderal Sudirman University has long implemented an Academic Information System to serve the academic activities of the academic community. The Academic Information System must be evaluated or tested in order to ensure the quality of the system which will affect the performance of the system. Software quality testing is carried out using the ISO 9126 standard method to identify software quality attributes with reference to five quality measures, namely functionality, reliability, usability, efficiency, and portability, and also tested using the Mean Opinion Score (MOS) method which is a method for measuring the performance and quality of applications built from the user's perspective, as well as testing website performance using GTMetrix. The results of testing the ISO 9126 method show